PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS KELAUTAN DAN PERIKANAN DAERAH PROVINSI SULAWESI TENGAH - Adia, Adia (Katalogis, 2017)
This research aims to find out motivation of participation, to know whether there is influence of motivation and how much influence of motivation to employee performance at maritime affairs and fishery area of central sulawesi province. the data were collected through observation method based on circumstance in the field and interviewe with respondents. Respondents in this research amounted to 114 people who came from various levels of rank. This research was conducted at the Department of marine and Fisheries Region of Central Sulawesi Province. The research method is quantitative analysis, the data obtained based on the questonnaire answer and then analyzed by the technique of multiple linear regression statistic, T test and F test. From the results of the research found that motivation has a significant positive effect on employee performance. Motivation with indicators includes communication, recognition, delegated authority and mutual concern together has positive and significant influence on employee performance on Department of Marine and Fisheries Region of Central Sulawesi Province. Simultaneously, the amount of contribution provided by the motivation variable and discipline on the employee performance based on calculation result was 65.2 percent.